2013
DOI: 10.1037/a0030585
|View full text |Cite
|
Sign up to set email alerts
|

The influence of moral disengagement and negative emotion on antisocial sport behavior.

Abstract: Given the prevalence of antisocial behavior in sport, researchers have begun to explore the role of self-regulatory processes in reducing such conduct. In this research, we examined the effects of moral disengagement on emotion and antisocial sport behavior. Specifically, we investigated whether moral disengagement facilitated antisocial behavior and whether this effect was mediated by anticipated feelings of guilt. Using a cross-sectional design, Study 1 found that the relationship between moral disengagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 32 publications
6
60
1
8
Order By: Relevance
“…These high scores were consistent with recent research in sport (e.g., Adie et al, 2013;Gunnell et al, 2013;Kipp & Weiss, 2013). Study 2 revealed overall low scores on perceived coach and teammate controlling climates, moral disengagement, and antisocial behavior; which was also consistent with recent research in sport (e.g., Bartholomew et al, 2010Boardley & Kavussanu, 2007Stanger et al, 2013). These SDT findings were positive given the evidence supporting adaptive psychological outcomes (e.g., subjective well-being, enjoyment, work/life satisfaction, less stress) stemming from autonomy-supportive climates and basic need satisfaction (Moreau & Mageau, 2012;.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These high scores were consistent with recent research in sport (e.g., Adie et al, 2013;Gunnell et al, 2013;Kipp & Weiss, 2013). Study 2 revealed overall low scores on perceived coach and teammate controlling climates, moral disengagement, and antisocial behavior; which was also consistent with recent research in sport (e.g., Bartholomew et al, 2010Boardley & Kavussanu, 2007Stanger et al, 2013). These SDT findings were positive given the evidence supporting adaptive psychological outcomes (e.g., subjective well-being, enjoyment, work/life satisfaction, less stress) stemming from autonomy-supportive climates and basic need satisfaction (Moreau & Mageau, 2012;.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, moral disengagement partially mediated the relation between both controlling coach and teammate climates and antisocial behavior towards both teammates and opponents (study 2; supporting hypothesis H2i). These moral disengagement findings reflected evidence from a number of studies that have substantiated the relation between moral disengagement and antisocial behaviors in sport Boardley et al, 2014;Corrion et al, 2009;Kavussanu et al, 2013;Stanger et al, 2013). Athletes who perceive their coach and/or teammates as being high on controlling behaviors may have higher levels of moral disengagement because they will have increased exposure to coaching/teammate behaviors that promote compliance with authority (e.g., coercion, obedience, conditional regard), rather than an internalization and subsequent self-regulation of moral values.…”
Section: Behaviorsupporting
confidence: 62%
See 2 more Smart Citations
“…Such deactivation enables behavior which violates personal standards to be performed because anticipatory guilt is reduced or not experienced. Indeed, it has been found that moral disengagement is associated with lower anticipatory guilt and higher engagement in transgressive behavior (Bandura et al, 1996;Stanger, Kavussanu, Boardley, & Ring, 2013). In line with this research and Bandura's self-regulatory model, it is expected that the relationship between personal standards and anticipatory guilt would vary as a function of underage drinking disengagement.…”
mentioning
confidence: 52%